ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE RASIO KEUANGAN PADA PERUSAHAAN LOGISTICS AND DELIVERIES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2021 - hadi, firdaus; Yudi; Muhammad Ridwan (Jambi Accounting Review (JAR), 2023)
This research aims to determine the financial performance of logistics and deliveries companies in 2020-2021 using the financial ratio method. In analyzing the data, researchers used quantitative methods. The sample in this research is logistics and deliveries companies listed on the Indonesia Stock Exchange in 2020-2021. The variables in this research consist of three ratios, namely liquidity, solvency and profitability. There are two sub ratios for each of these ratios (current ratio and cash ratio), (debt to asset ratio and debt to equity ratio), (return on investment and return on equity). The results of the research show that analysis using liquidity ratios and profitability ratios found that the company's performance was not in good condition, then analysis using the solvency ratio found that the company's performance was in good condition.